Polygenic risk score models based on anxiety-related traits as endophenotypes to predict unipolar depression and suicidal behavior - A. V. Kazantseva; R. F. Enikeeva; Yu. D. Davydova; R. G. Valinurov; I. Yu. Ahmerova I.Yu.; S. B. Malykh; M. M. Lobaskova; E. K. Khusnutdinova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The present study included the construction of polygenic risk score (PRS) models of individual differences in anxiety level, which increased values represent the endophenotype of depression and suicidal behavior, to predict these psychopathologies based on genotyping of 63 SNPs of serotoninergic, hypothalamicpituitary-adrenal and neurotrophic factors systems together with the relative leukocyte telomere length. According to logistic regression analysis, PRS models of individual differences in Neuroticism (EPI) level (P<0,2) predicted decreased risk of unipolar depression (P0.2=0,033, β=-5,24, r2=0,78) in women, which points to the necessity to consider sex during polygenic risk score analysis.